Effect of Adding Different Concentrations of Sodium Hypochlorite in Drinking Water on Blood Serum Albumins and Globulins of Broilers - Al-Hemairi, Atika A. R. (The Iraqi Journal of Veterinary Medicine, 2012)
The study was conducted to investigate the effect of different concentrations of sodium hypochlorite (sodium dichloro iso cyanurate) in the drinking water on the percentages of serum proteins of broilers chicks at 4 and 7 weeks of age. Two hundred forty Hubbard chicks one day – old aged were divided randomly into four equal groups, each group was divided into two replicate. The four groups were as follows: Treatment 1: Adding 6.68 mg /liter water of sodium dichloro iso cyanurate to drinking water. Treatment 2: Adding 13.36 mg /liter water of sodium dichloro iso cyanurate to drinking water. Treatment 3: Adding 20.04 mg /liter water of sodium dichloro iso cyanurate to drinking water. Treatment 4: Supplying water without any additive (control 1). The results revealed that: Adding sodium dichloro iso cyanurate (T1, T2 and T3) increased significantly (P<0.05) broilers blood serum albumin ,total albumins , - globulin and total globulins at 4 and 7 weeks of age, in the same time no differences appeared in the others compared with control group . this indicated of the importance of adding sodium dichloro iso cyanurate to enhance broilers health.